The Effect of Special Strength Training Of Working Muscles During Running On The Development of Some Biomechanical Variables and Achievement 100m dash for Youth - Nagim, Jamila; Al-Sudani, Ali (Journal of Physical Education, 2020)
The research aimed at designing special strength training for working muscles using rubber ropes, weights, rebound jumping, and free weights to develop some biomechanical variables (force, momentum, and pressure ) as all as identifying the effect of these exercises on developing these biomechanical variables and accomplishing a 100-meter run for young people. The researchers used the experimental method and the subjects were (6) athletes from the national center for gifted in athletics in 100m dash. The training program was applied for (8) weeks including 24 training sessions with 3 training sessions per week. The results showed that these exercises have a great effect on developing achievement as well as some biomechanical variables The exercises using the auxiliary tools and tools according to the performance that were used in the special strength exercises developed for them are effective in developing the achievement.